PENGEMBANGAN BAHAN AJAR BERBASIS KEARIFAN LOKAL UNTUK PEMBELAJARAN IPA DAN IPS DI KELAS IV SDN 17 PONTIANAK KOTA - Santoso, Ichsan; Kresnadi, Hery; Ghasya, Dyoty Auliya (Universitas Tanjungpura, 2025)
This study aims to develop teaching materials based on local wisdom for natural and social science learning, specifically Chapter 6,